Heat Stress Impedes Development and Lowers Fecundity of the Brown Planthopper Nilaparvata lugens (Stål) - Piyaphongkul, Jiranan; Pritchard, Jeremy; Bale, Jeff (PLOS ONE, 2012)
This study investigated the effects of sub-lethal high temperatures on the development and reproduction of the brown plant hopper Nilaparvata lugens (Stål). When first instar nymphs were exposed at their ULT50 (41.8°C) mean development time to adult was increased in both males and females, from 15.2±0.3 and 18.2±0.3 days respectively in the control to 18.7±0.2 and 19±0.2 days in the treated insects. These differences in development arising from heat stress experienced in the first instar nymph did not persist into the adult stage (adult longevity of 23.5±1.1 and 24.4±1.1 days for treated males and females compared with 25.7±1.0 and 20.6±1.1 days in the control groups), although untreated males lived longer than untreated females. Total mean longevity was increased from 38.8±0.1 to 43.4±1.0 days in treated females, but male longevity was not affected (40.9±0.9 and 42.2±1.1 days respectively). When male and female first instar nymphs were exposed at their ULT50 of 41.8°C and allowed to mate on reaching adult, mean fecundity was reduced from 403.8±13.7 to 128.0±16.6 eggs per female in the treated insects. Following exposure of adult insects at their equivalent ULT50 (42.5°C), the three mating combinations of treated male x treated female, treated male x untreated female, and untreated male x treated female produced 169.3±14.7, 249.6±21.3 and 233.4±17.2 eggs per female respectively, all significantly lower than the control. Exposure of nymphs and adults at their respective ULT50 temperatures also significantly extended the time required for their progeny to complete egg development for all mating combinations compared with control. Overall, sub-lethal heat stress inhibited nymphal development, lowered fecundity and extended egg development time.